Privacy as life, liberty, property - Volkman, Richard (Ethics and Information Technology, 2003)
The cluster of concerns usually identified as matters of privacy can be adequately accounted for by unpacking our natural rights to life, liberty, and property. Privacy as derived from fundamental natural rights to life, liberty, and property encompasses the advantages of the control and restricted access theories without their attendant difficulties., (C)2003 Kluwer Academic Publishers
28 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-294-459-957-177 tex.type: [object Object]
Keywords: Access control; Data privacy; Information technology; Judith Thomson; Natural rights; Privacy; Right to privacies; Right to privacy; Social sciences; Thomson; dept.phi; natural rights; privacy; right to privacy